Advanced Cross-Correlation Function Application to Identify Arterial Baroreflex Sensitivity Variations From Healthy to Diabetes Mellitus - Yeh, Shoou-Jeng; Lung, Chi-Wen; Jan, Yih-Kuen; Liau, Ben-Yi (Frontiers in Neuroscience, 2022)
Diabetes mellitus (DM) is a chronic disease in which insulin cannot regulate blood sugar in the human body. The WHO team announced that DM is a widespread and challenging health problem due to its high growth prevalence and impact on national economies. In addition, autonomic neuropathy (AN) is one of the common diabetic complications. It can induce cardiovascular diseases and influence the bio-feedback mechanism, ex. Baroreflex (BRS). BRS is an important bio-mechanism that maintains a stable circulatory system via the autonomic nervous system. Therefore, an irregular autonomic nervous system would lead to imbalanced BRS. However, autonomic neuropathy syndrome requires lots of exams in clinical practice. We therefore propose an advanced cross-correlation function (ACCF) method with suitable threshold parameters to assess changes in BRS using the relationship between blood pressure and heart rate in healthy→ DM-only → DM with AN progress for early clinical diagnosis. The ACCF analysis results with thresholds that revealed that healthy and DM groups had different qualified percentages of significant maximum CCF value (p<0.05). Thus, the influence effect of DM on BRS is revealed. The maximum CCF index results showed the healthy group could be separated from DM groups (p<0.05). Therefore, the phase change between HR and BP is indicated in DM groups. This is a pilot study that analyzes BRS control variation in healthy and DM subjects using ACCF. ACCF analysis with suitable threshold parameters could explore the hidden circulatory system component characteristics and BRS performance in DM patients. The superiority of this ACCF algorithm is useful in distinguishing whether DM has AN or not.